2017
DOI: 10.3847/1538-4365/aa6476
|View full text |Cite
|
Sign up to set email alerts
|

A Herschel Space Observatory Spectral Line Survey of Local Luminous Infrared Galaxies from 194 to 671 Microns

Abstract: We describe a Herschel Space Observatory 194-671 μm spectroscopic survey of a sample of 121 local luminous infrared galaxies and report the fluxes of the CO J to J-1 rotational transitions for   J 4 13, the [N II] 205 μm line, the [C I] lines at 609 and 370 μm, as well as additional and usually fainter lines. The CO spectral line energy distributions (SLEDs) presented here are consistent with our earlier work, which was based on a smaller sample, that calls for two distinct molecular gas components in genera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
129
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(137 citation statements)
references
References 132 publications
8
129
0
Order By: Relevance
“…We note that we do not apply the correction factors to the [N II] 205 μm emission based on the FIR color of galaxies provided in Lu et al (2017). We use instead the original, point-source calibrated fluxes since we do not use those corrections in our Herschel/PACS data.…”
Section: Discussionmentioning
confidence: 99%
“…We note that we do not apply the correction factors to the [N II] 205 μm emission based on the FIR color of galaxies provided in Lu et al (2017). We use instead the original, point-source calibrated fluxes since we do not use those corrections in our Herschel/PACS data.…”
Section: Discussionmentioning
confidence: 99%
“…Its molecular gas excitation hints at the ex- istence of a strong heating source. To account for the strong mid-J CO lines observed in NGC 253 and NGC 891, both Hailey-Dunsheath et al (2008); Nikola et al (2011) both invoke the need for strong mechanical heating/shocks from a turbulent star-forming environment (see also Kamenetzky et al 2016;Lu et al 2017). The high-J turnover (at Jup ≥ 5) and tail of the CO SLED indicates that the CO excitation is, however, not as extreme as in the highly excited QSO systems (Weiß et al 2007;Salomé et al 2012).…”
Section: Co Spectral Line Energy Distributionmentioning
confidence: 99%
“…Using the SPIFI spectrometer on the AST/RO telescope at South Pole, Oberst et al (2006Oberst et al ( , 2011 (Goldsmith et al 2015), and demonstrated that most of the [Nii] line arises from extended, low density (n e − ∼ 10 to 50 cm −3 ) Hii regions. Other efforts to use [Nii] to derive average electron densities have been made in a range of local galaxies (n e − ∼ 20-100 cm −3 ), for instance: M51 and Centaurs A, (Parkin et al 2013), Ultra-luminous Infrared Galaxies ULIRGs (HERUS sample;Farrah et al 2013), Dwarf galaxies (Cormier et al 2015), KINGFISH galaxies (Herrera-Camus et al 2016) and other SFGs (Lu et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The newly determined multi-transition 12 COto-13 CO isotopologue ratios allow us to determine more accurately the CO gas column densities and their relation to the much more abundant H 2 gas, including the values of X in a large number of galaxy central regions. The analysis of the 12 CO and 13 CO spectral lines is of particular importance in the interpretation of the Herschel Space Observatory (2009-2013) observations of galaxies in the two submillimeter [CI] lines and the farinfrared [CII] line (Israel et al 2015;Kamenetzky et al 2016;Fernández-Ontiveros et al 2016;Lu et al 2017;Croxall et al 2017;Díaz-Santos et al 2017;and Herrera-Camus et al 2018). With it, we will place significant constraints on the relation between molecular and atomic carbon and determine the carbon budget in the observed galaxy centers.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 13CO fraction of all C6.2. Neutral atomic carbon fractionWe took central[CI] line data from the compilations byIsrael et al (2015),Kamenetzky et al (2016), andLu et al (2017).…”
mentioning
confidence: 99%